2020
DOI: 10.1038/s42255-020-0217-6
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamines suppress fatty acid re-esterification and increase oxidation in white adipocytes via STAT3

Abstract: Catecholamines stimulate the mobilization of stored triglycerides in adipocytes to provide fatty acids (FAs) for other tissues. However, a large proportion is taken back up and either oxidized or re-esterified. What controls the disposition of these FAs in adipocytes remains unknown. Here we report that catecholamines redirect FAs for oxidation through the phosphorylation of signal transducer and activator of transcription 3 (STAT3). Adipocyte STAT3 is phosphorylated upon activation of β-adrenergic receptors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 136 publications
(60 reference statements)
1
21
0
Order By: Relevance
“…This might facilitate a finely tuned management of triacylglycerol synthesis and breakdown, that varies rapidly between bouts of energy intake (post-prandial periods) or energy dissipation (exercise, fasting, cold exposure). Besides providing FA for other tissues via their lipolytic effect, catecholamines have recently been described to also increase FA oxidation rate in the adipocytes themselves, via the phosphorylation of signal transducer and activator of transcription 3 (STAT3), which, in turn regulates FA metabolism in a non-genomic manner[ 62 ]. Alongside these two fates of released FA, mobilization and oxidation, there is also a third way, consisting in FA reesterification, which is predominant in adipocytes, since it limits excessive FA release and subsequent lipotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…This might facilitate a finely tuned management of triacylglycerol synthesis and breakdown, that varies rapidly between bouts of energy intake (post-prandial periods) or energy dissipation (exercise, fasting, cold exposure). Besides providing FA for other tissues via their lipolytic effect, catecholamines have recently been described to also increase FA oxidation rate in the adipocytes themselves, via the phosphorylation of signal transducer and activator of transcription 3 (STAT3), which, in turn regulates FA metabolism in a non-genomic manner[ 62 ]. Alongside these two fates of released FA, mobilization and oxidation, there is also a third way, consisting in FA reesterification, which is predominant in adipocytes, since it limits excessive FA release and subsequent lipotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The constant breakdown and release of FFAs from adipocytes has been observed in fasting in rats, mice, and humans, with 40% of FFAs being rapidly recycled back to triglycerides [ 54 ]. More recently, it has been shown that β 3 AR signaling blocks the re-esterification of FFAs to TGs, potentially allowing for an inter-organ GL/FFA cycle [ 55 ].…”
Section: Inter-organ Lipid Signaling From White Adipose Tissuementioning
confidence: 99%
“…The hyperactivation of neurohormonal systems especially β-adrenergic receptors (βARs) signaling abnormalities plays a pivotal role in HF pathogenesis 59 . And activated βARs directly lead to the phosphorylation of signal transducer and activator of transcription 3 (Stat3) which integrates multiple signaling pathways in the development of cardiac hypertrophy and eventual heart failure in cardiomyocytes 60 . Zhang et al investigated the molecular mechanism underlying βAR-mediated Stat3 activation and then proved that Src, Yes and Fyn, the main SFKs in MEF cells were critical mediators for βAR-initiated Stat3 phosphorylation to maintain the physiological function of the heart 61 .…”
Section: Sfks and Cardiovascular Diseasesmentioning
confidence: 99%